PETRA, MSVAT-SPACE and SEMAC sequences for metal artefact reduction in dental MR imaging - Hilgenfeld, Tim; Prager, Marcel; Heil, Alexander; Schwindling, Franz Sebastian; Rammelsberg, Peter; Bendszus, Martin; Heiland, Sabine (European radiology, 2017)
Objectives: Dental MRI is often impaired by artefacts due to metallic dental materials. Several sequences were developed to reduce susceptibility artefacts. Here, we evaluated a set of sequences for artefact reduction for dental MRI for the first time.Methods: Artefact volume, signal-to-noise ratio (SNR) and image quality were assessed on a 3-T MRI for pointwise encoding time reduction with radial acquisition (PETRA), multiple-slab acquisition with view angle tilting gradient, based on a sampling perfection with application-optimised contrasts using different flip angle evolution (SPACE) sequence (MSVAT-SPACE), slice-encoding for metal-artefact correction (SEMAC) and compared to a standard SPACE and a standard turbo-spin-echo (TSE) sequence. Field-of-view and acquisition times were chosen to enable in vivo application. Two implant-supported prostheses were tested (porcelain fused to metal non-precious alloy and monolithic zirconia). Results: Smallest artefact was measured for TSE sequences with no difference between the standard TSE and the SEMAC. MSVAT-SPACE reduced artefacts about 56% compared to the standard SPACE. Effect of the PETRA was dependent on sample used. Image quality and SNR were comparable for all sequences except PETRA, which yielded poor results. Conclusion: There is no benefit in terms of artefact reduction for SEMAC compared to standard TSE. Usage of MSVAT-SPACE is advantageous since artefacts are reduced and higher resolution is achieved. Key Points: SEMAC is not superior to TSE in terms of artefact reduction. MSVAT-SPACE reduces susceptibility artefacts while maintaining comparable image quality.PETRA reduces susceptibility artefacts depending on material but offers poor image quality
First online: 11 July 2017
Gesehen am 21.06.2018